Antidiabetic activity evaluation of Onobrychis species on alloxan-induced diabetic mice - Hanefi Ozbek; Ozlem Bahadir Acikara; Burcin Ergene Oz; Serkan Ozbilgin; Neriman Ipek Kirmizi; Bade Cevriye Ozrenk; Mehmet Tekin; Gulcin Saltan
In the current study, four Onobrychis species, O. albiflora Hub.-Mor., O. argyrea Boiss. subsp. argyrea Boiss., O. galegifolia Boiss., and O. tournefortii (Willd.) Desv. were collected from Anatolia to be evaluated for their antidiabetic activities. Methanol water extracts of the aerial parts were used for experiments. An alloxan-induced diabetic mice test model was used. Phytochemical analysis of the tested extracts was investigated using the HPLC method. The highest activity was observed with treatment of O. albiflora aerial part extract. Significant decrements were detected in the blood glucose levels as follows: 180.83±47.48 and 252.83±50.47mg/dL at 100 mg/kg and 200 mg/kg doses of O. albiflora, respectively, when compared to the isotonic saline solution control group, eliciting a blood glucose level of 494.20±27.32. Among the tested standard compounds, rutin and isoquercetin were detected in the examined species. The highest amount of rutin (1.1981±0.0017%) and isoquercetin (0.7318±0.0197%) were found in O. albiflora and O. argyrea subsp. argyrea, respectively. Antidiabetic activities of the tested Onobrychis species seem to indicate a possible correlation with their rutin and isoquercetin contents. Therefore, rutin and isoquercetin may be the antidiabetic compounds that contribute to the antidiabetic activity of the tested Onobrychis species.